Lipid oxidation in margarine emulsions - I. Pokorná; V. Filip; J. Šmidrkal (Czech Journal of Food Sciences, 2004)
Influence of different storage atmosphere (argon and oxygen atmosphere) and influence of monoacylglycerol's emulsifier (with the carbon chain containing 10, 12, 14, 16, 18 carbon atoms and commercial emulsifier D and a model mixture of monoacylglycerols with the carbon chains containing 10, 12, 14 carbon atoms) on lipid oxidation in margarine emulsions were observed. The rate of lipid oxidation in emulsion with oxygen atmosphere depends on oxygen diffusion through the emulsion layer, while lipid oxidation in emulsion with inert atmosphere is influenced by initial oxygen concentration in water and fat phase. Lipid oxidation in emulsion also depends on acyl combination and the acyl length in emulsifier. Emulsions with monostearoylglycerol oxidized minimally while emulsions with a mixture of monoacylglycerols oxidized maximally.